Relationship between social capital and test seeking among blood donors in Brazil. Issue 2 (15th August 2012) - Oliveira, C. D. L.; Goncalez, T.; Wright, D.; Rocha, P. C.; Miranda, C.; Capuani, L.; Carneiro‐Proietti, A. B.; Proietti, F. A.; de Almeida‐Neto, C.; Larsen, N. M.; Sampaio, D.; Custer, B.; et al.
<x xml:space="preserve">Abstract</x> Background and Objectives Higher risk of HIV infection could be associated with test seeking, which is one motivation for donating blood. Cognitive social capital is defined as the social support, trust and co‐operation that guide community behaviour. Structural social capital refers to an individual's participation in institutions and organizations. The association between social capital and test seeking was assessed. Materials and Methods A survey of over 7500 donors in three Brazilian blood centres was conducted. Test seeking was classified into four non‐overlapping categories (non‐test seeker, possible, presumed and self‐disclosed test seekers) using one direct and two indirect questions. Social capital was summarized into cognitive and structural categorizations. Multivariable logistic regression analysis was performed. Results Compared with non‐test seekers (62% of survey respondents), cognitive social capital was higher for each category of test seeking (OR = 1.1, 7.4, 7.1, P < 0.05 respectively). Male gender, lower education and lower income were also significantly associated with test seeking. Conclusion As test seekers appear to have strong social networks, blood banks may leverage this to convince them to seek testing at other locations.